MEMBANGUN TATA KELOLA SEKOLAH KATOLIK YANG DIJIWAI OLEH SEMANGAT INJIL - Panjaitan, Sinta Cristin; Wilhelmus, Ola Rongan (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2019)
This study conducted to explore varius aspects and components of the Catholic school governance and how those aspects and elements have been truly inspired by the spirit of the Holy Gospel throughout daily education praxices. This study applied a qualitative method. Data collection was carried out by individual interview. However, the researcher then took her own initiative to construct a series of questionnaire for a student comparison data purpose.There were 60 students asked to fill out the questionaires. The result of this study indicatedthat the catholic educators played a very important role in developing Catholic school governance inspired by the spirit of the Holy Gospel. By paying an intensive attention inmanaging various components of the Catholic school based on the spirit of the Holy Gospel then the Catholic Church must be optimistic that the Catholic schools can survive in the future.